Preparation and isolation of amine (organo) chromium (iii) complexes in alcoholic media - Crouse, Karen Ann; Goh , Lai Yoong (Elsevier, 1982)
σ-Bonded organochromium complexes are prepared by the reaction of the 2- and 3-pyridylmethyl chlorides (picolyl chlorides) with bis(amine)chromium(II) ions, where amine = en, ethylenediamine; dap, 1,3-diaminopropane and trien, triethylenetetramine, in alcoholic media. The air-stable species are isolated as hydrated chlorides of the pyridylmethyl complexes, 2- and 3-NC5H4CH2Cr(amine)2(H2O)2m and the N-protonated pyridiomethyl complexes 2- and 3-HN+C5H4CH2Cr(amine)2(H2O)2+m (m = 1 for amine = en and dap and m = 0 for amine = trien). Characterisation was by elemental analysis, absorption spectra and product analyses of their decomposition in dilute aqueous solution.